Simulation study of the effects of interstitial fluid pressure and blood flow velocity on transvascular transport of nanoparticles in tumor microenvironment. (September 2020) - Gao, Yan; Shi, Yanbin; Fu, Mengguang; Feng, Yihua; Lin, Guimei; Kong, Deyin; Jiang, Bo
Highlights: We analyzed the influence factors during transvascular transport of nanodrugs. The transport process of nanodrugs was simulated by computational fluid dynamics. The effect of interstitial fluid pressure on the transport process was studied. The effect of blood flow velocity on the transport process was explored. Abstract: Background and objective: Although nanoparticle preparations have great potential in the treatment of tumors, nanoparticle preparations have not achieved the desired therapeutic effect. The reason is that the abnormal tumor microenvironment prevents nanoparticles from effective concentrating and reaching tumor area. Therefore, it's very necessary to better understand the effect of the abnormal tumor microenvironment on the transvascular transport of nanoparticles to overcome this critical problem. Methods: In this paper, a tumor abnormal vascular-interstitial model was established, and the transvascular transport process of nanoparticles was simulated in the model by computational fluid dynamics (CFD) modeling. Results: The simulation results showed that the transport efficiency of nanoparticles decreased with increasing interstitial fluid pressure (IFP), and nanoparticles could not cross the blood vessel wall when the IFP approached the blood vessel wall pressure. Interestingly, the transport efficiency of nanoparticles first increased with blood flow velocity, and then decreased with blood flow velocity. Conclusions: The results showed that with the continuous malignant development of tumors, the ability of nanoparticles to passively diffuse has almost disappeared. The enhanced permeability and retention (EPR) effect of the nanoparticles disappeared with the disappearance of the pressure gradient inside the tumor. These results provided guidance for future research on the vascular transport pathways and mechanisms of nanoparticles. Graphical abstract: Image, graphical abstract